2020
DOI: 10.3390/ijms21041212
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids Transport and Metabolism 2.0

Abstract: This editorial aims to summarize the 19 scientific papers that contributed to this Special Issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Additionally, we confirmed that strain CJN36-1N T has a few more genes in the 'amino acid transport and metabolism' and 'inorganic ion transport and metabolism' section of COG categories compared to its closely related species (Table S1). This indicates the organism's cells have an enhanced ability to metabolize inorganic ions and amino acids, adapting more effectively to their environment [32,33].…”
Section: Genomic Featuresmentioning
confidence: 99%
“…Additionally, we confirmed that strain CJN36-1N T has a few more genes in the 'amino acid transport and metabolism' and 'inorganic ion transport and metabolism' section of COG categories compared to its closely related species (Table S1). This indicates the organism's cells have an enhanced ability to metabolize inorganic ions and amino acids, adapting more effectively to their environment [32,33].…”
Section: Genomic Featuresmentioning
confidence: 99%
“…They are also precursors of secondary metabolites, which are essential for plant growth and development. Abiotic and biotic stresses are also discussed concerning amino acids [ 9 ]. Plants get nitrogen from amino acids and uptake from soil by the roots and transport to leaves as well as to other organs via the phloem.…”
Section: Introductionmentioning
confidence: 99%
“…The AAT gene family has been systematically identified in many plants [53][54][55]. Due to the complex genomic structure of cotton, little is known about AAT genes in cotton.…”
Section: Introductionmentioning
confidence: 99%